An atypical presentation of a re-emerging disease. Issue 1 (2nd January 2017) - Hunter, Michael; Brine, Patrick
ABSTRACT: Often referred to as 'The Great Mimicker', syphilis infections have been on the rise since 2000 including cases of primary and secondary syphilis where 19, 999 were reported in the USA in 2014. ​​The increase in cases has led the USPSTF to recommend screening for syphilis infection in persons who are at increased risk of infection. ​​Changes in screening and re-emergence of the disease necessitates review of the multitude of circumstances a patient can present for care. Immunocompetent patients begin to show classic symptoms within 10–90 days following infection with the spirochete. In the immunocompromised patient, the presenting symptoms are often atypical and more complex. With the rise in HIV infections, syphilitic infections have become increasingly common worldwide and several atypical presentations have been observed. ​​The following case is an atypical presentation of syphilis involving both central and peripheral nervous system findings in a patient without significant medical history.